Pathologic Fractures: A Neglected Clinical Feature of Parathyroid Adenoma - Hassan Abshirini; Iran Rashidi; Nader Saki (Case Reports in Medicine)
The pattern of clinical presentation of primary hyperparathyroidism (pHPT) has changed dramatically from a severe disease to an asymptomatic condition in Western countries. The story is completely different in Eastern countries. Bone and joint related sign and symptoms like bone pain and multiple fractures are common in these patients. Imaging and nuclear medicine studies will be helpful specially in patient who candidate for surgical removal of the abnormal parathyroid gland. Here, we present a 48-year-old man with multiple typical fractures in long bones and a single adenoma in his right inferior parathyroid gland. pHPT is a severe, symptomatic disease with serious complications and high morbidity in Iran. Advanced skeletal disease is the most common pattern of presentation.